Forward bias capacitance investigation as a powerful tool to monitor graphene/silicon interfaces. (15th September 2021) - Matacena, Ilaria; Guerriero, Pierluigi; Lancellotti, Laura; Bobeico, Eugenia; Lisi, Nicola; Chierchia, Rosa; Delli Veneri, Paola; Daliento, Santolo
Highlights: Forward bias capacitance is a powerful method for interface properties monitoring. Effectiveness of nitric acid doping is proved by multiple peaks disappearance. Nitric acid doping is effective in reducing defects in graphene/silicon solar cells. Capacitance peak position is mainly influenced by saturation current. Capacitance peak height is mainly influenced by series resistance. Abstract: In this paper a technique based on the analysis of forward bias capacitance for interface characterization in Schottky structure is proposed. In particular, the occurrence of multiple peaks in the capacitance-voltage curve was related to non-uniform properties of the interfaces, for instance undesired localized interface defects. A graphene/silicon solar cell is considered as case of study. Experimental forward bias capacitance-voltage curve exhibits multiple peaks, thus suggesting the occurrence of interface defects. A numerical model of the solar cell was implemented in TCAD environment considering non-uniform interface properties. The model was calibrated to describe the experimental behavior and allowing to extract the defects distribution. HNO3 doping in graphene was exploited to reduce defects. The effectiveness of this approach was proved comparing experimental capacitance before and after doping.